Resistance to Fluopicolide and Propamocarb and Baseline Sensitivity to Ethaboxam Among Isolates of Pseudoperonospora cubensis From the Eastern United States - Thomas, A (Plant disease, 2018)
Chemical control is currently the most effective method for controlling cucurbit downy mildew (CDM) caused by Pseudoperonospora cubensis. Most commercial cucurbit cultivars, with the exception of a few new cucumber cultivars, lack adequate disease resistance. Fluopicolide and propamocarb were among the most effective fungicides against CDM in the United States between 2006 and 2009. Since then, reduced efficacy of these two fungicides under field conditions was reported starting around 2013 but occurrence of resistance to fluopicolide and propamocarb in field isolates of P. cubensis had not been established. Thirty-one isolates collected from cucurbits in the eastern United States were tested for their sensitivity to fluopicolide and propamocarb using a leaf disc assay. This same set of isolates and four additional isolates (i.e., 35 isolates) were also used to establish the baseline sensitivity of P. cubensis to ethaboxam, an ethylamino-thiazole-carboxamide fungicide, which was recently granted registration to control CDM in the United States. About 65% of the isolates tested were resistant to fluopicolide with at least one resistant isolate being present in samples collected from 12 of the 13 states in the eastern United States. About 74% of the isolates tested were sensitive to propamocarb with at least one resistant isolate being among samples collected from 8 of the 12 states in the study. The frequency of resistance to fluopicolide and propamocarb was high among isolates collected from cucumber, while the frequency was low among isolates collected from other cucurbit host types. All isolates tested were found to be sensitive to ethaboxam and EC50 values ranged from 0.18 to 3.08 mg a.i./liter with a median of 1.55 mg a.i./liter. The ratio of EC50 values for the least sensitive and the most sensitive isolate was 17.1, indicating that P. cubensis isolates were highly sensitive to ethaboxam. The most sensitive isolates to ethaboxam were collected from New York, North Carolina, and Ohio, while the least sensitive isolates were collected from Georgia, Michigan, and New Jersey. These results show that ethaboxam could be a viable addition to fungicide programs used to control CDM in the United States